Skeleton-based human activity understanding - Liu, Jun (2019)
Human activity understanding is an important research problem due to its relevance to a wide range of applications. Recently, 3D skeleton-based activity analysis becomes popular due to its succinctness, robustness, and view-invariant representation. In this thesis, we focus on human activity understanding in 3D skeleton sequences.